The Implementation of Reading Text Strategies in Enhancing EFL Learners Vocabularies: A Case of One Islamic Higher Education in Jambi, Indonesia - Toni Indrayadi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
The purpose of this study was to reveal the lecturer’s strategy in enhancing students’ English vocabularies in the process of teaching and learning in the classroom. 3 English lecturers who have ever taught English for Academic Purposes (EAP) in non-English department were involved in this study. The data were collected through semi-structure interview. Thematic analysis was applied for analysis the participants’ interview result. Finding of this study show that; first. the participants used selected reading text as a media of enhancing students vocabularies. Second, the strategy was implemented through small group discussion and pair work to make students actively participated in sharing the knowledge. Third, the participants evaluated the students’ understanding of reading text strategy by asking them to work individually without any assistance from the group members This study recommended that the findings can be a basis consideration in enhancing students’ vocabularies in the process of teaching and learning.